2021
DOI: 10.1016/j.jsames.2020.102978
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of temperature, salinity and chlorophyll-a in the Magdalena River mouth, Caribbean Sea

Abstract: Variations in the physico-chemical characteristics of estuaries, such as surface water salinity and temperature, lead to the establishment of gradients that are closely related with the distribution of nutrients and suspended sediment. This affects light penetration, which in turn influences Chlorophyll-a (Chl-a) concentration and primary productivity. We used MODIS imagery to identify spatio-temporal patterns of sea surface salinity, temperature, and Chl-a concentrations from 2003 to 2017, to explore relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…It has been observed that these Belize coastal plumes can be comprised of a variety of constituents, including sediments, agricultural runoff, and sewage (Maidens and Burke, 2005;Macintyre et al, 2009;Emrich et al, 2017;Wells et al, 2019), with Soto et al (2009) observing a consistent year-to-year river plume occurrences with coral ecosystems (Soto et al, 2009). Though classified as oligotrophic, river plumes can often cause Caribbean waters to become mesotrophic (Warne et al, 2005;Torregroza-Espinosa et al, 2021). In Belize, New River is known to cause a decline in water quality affecting surrounding corals due to poor farming practices and deforestation (Espinoza-Avalos et al, 2009;Reyes et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that these Belize coastal plumes can be comprised of a variety of constituents, including sediments, agricultural runoff, and sewage (Maidens and Burke, 2005;Macintyre et al, 2009;Emrich et al, 2017;Wells et al, 2019), with Soto et al (2009) observing a consistent year-to-year river plume occurrences with coral ecosystems (Soto et al, 2009). Though classified as oligotrophic, river plumes can often cause Caribbean waters to become mesotrophic (Warne et al, 2005;Torregroza-Espinosa et al, 2021). In Belize, New River is known to cause a decline in water quality affecting surrounding corals due to poor farming practices and deforestation (Espinoza-Avalos et al, 2009;Reyes et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This occurs because ocean-atmosphere climate interactions, such as those resulting from the ENSO, affect the sea level, SST, air temperature, chlorophyll-a, and upwelling intensity. During the El Niño period, the upwelling intensity increased, followed by an increase in the chlorophyll-a concentration; in contrast, during the La Niña period, the upwelling intensity decreased followed by a decrease in the chlorophyll-a concentration [26,[82][83][84][85].…”
Section: Impact Of the 2011 La Niña And 2015 El Niño Phenomena On The...mentioning
confidence: 99%
“…8) shows two main periodic peaks that were related to warmer water registered in summer (January to March) and spring (September to December) seasons which could lead to algal growth (Bonansea et al, 2019). Although urbanization and agriculture activities have generated an economic development for the region, different studies suggest that watersheds are extremely sensitive to an increase in intensive land use classes with significant impacts on eutrophication and water quality of aquatic environments, including rivers, lakes and reservoirs (Welde and Gebremariam, 2017;Desta and Fetene, 2020;Kiage and Douglas, 2020;Torregroza-Espinosa et al, 2020;Wei et al, 2020). During the process of urbanization, a permeable vegetated land surface is replaced by concrete and other impervious materials which can drastically transform surface hydrological processes altering the balance between infiltration and runoff.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Advances in remote sensing technology have considerably improved the assessment of a long time-series of LULC change (Huang et al, 2002;Fukushima et al, 2007;Huang et al, 2014;Loveland and Irons, 2016;Gómez et al, 2016;Wei et al, 2020), variations in water quality (Tebbs et al, 2013;Chen et al, 2014;Villa et al, 2014;González-Márquez et al, 2018;Zhou et al, 2018;Bonansea et al, 2019;Elhag et al, 2019;Germán et al, 2020;Kiage and Douglas, 2020;Li et al, 2020, Torregroza-Espinosa, et al 2020) and eutrophication causes (Smith and Schindler, 2009;Mendoza et al, 2015;Padedda et al, 2017;Bhagowati and Ahamad, 2019;Le Moal et al, 2019;Cai et al, 2020). However, to the best of our knowledge, studies that relate LULC change and reservoir water quality are scarce and dispersed, particularly in the Southern hemisphere.…”
Section: Introductionmentioning
confidence: 99%